NILAI-NILAI KEARIFAN LOKAL PADA RITUS KELAHIRAN DALAM KEHIDUPAN ETNIS SASAK DALAM MEMBENTUK PERILAKU SOSIAL SISWA MELALUI PEMBELAJARAN IPAS DI SD - Dini Hariani; Habibuddin; Husnul Mukti; Burhanuddin (STKIP Subang, 2024)
This research aims to: (1) identify and reflect local wisdom values ​​that are included in birth rites in the life of the Sasak ethnic group; (2) explain the integration of local wisdom values ​​in birth rites in the lives of the Sasak ethnic group through science learning in class; (3) explain the integration of local wisdom values ​​in birth rites in Sasak ethnic life which can shape students' social behavior.This research employed a descriptive qualitative approach. The research was conducted in Kotaraja Village and at SD Negeri 2 Kotaraja with research subjects as community leaders, school principals, teachers and students. Data collection techniques used observation, interviews and documentation. Test the validity of the data using credibility testing with source triangulation techniques in various ways and at various times. Data analysis utilized interactive model analysis from Miles & Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The results of research on local wisdom values ​​in birth rites in Sasak ethnic life in shaping students' social behavior through science learning at SD Negeri 2 Kotaraja, namely the values ​​of the circumcision rite: (1) the value of togetherness; (2) family values; (3) the value of mutual cooperation and (4) the value of love for one's country and local wisdom. Meanwhile, the integration of local wisdom values ​​in the birth rite of circumcision in shaping students' social behavior in the school environment through the implementation of school programs and the implementation of learning using group learning methods, especially in social and natural science learning in the classroom. The social behavior that is formed through the integration of local wisdom values ​​of Praja Sunatan includes students respecting other people's opinions, students can learn to be responsible for the mandate given, students have an attitude of mutual cooperation, students have an attitude of helping each other in solving problems, students can respect local wisdom in the surrounding area by preserving and protecting it.